145k views
2 votes
Can someone help me pls? (-10)² - (9 + 5 • 3) pls help ;-;

User Jhauberg
by
5.3k points

1 Answer

1 vote

Steps:

(−10)2−(9+(5)(3))

=100−(9+(5)(3))

=100−(9+15)

=100−24

=76

Solve:

(−10)2−(9+(5)(3))

=76

Description:

The first step is to simplify the equation step by step and to simplify an equation you can first multiplying the factors and use the exponent rules to remove the parentheses. After that you need to combine it a terms. Then you will get your answer.

Since this was a small equation. It was easy to simplify, Steps are above.

Answer: =76

Hope this helps.

User Nrzonline
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.